Hookworm infection modulates lung and intestinal transcriptomic responses to SARS-CoV-2 in Syrian hamsters - Rosa, Bruce A.; Bigham, Mahdiyeh; Darling, Tamarand L.; Arun, Ashutosh; Singh, Kumar Sachin; Martin, John; Boon, Adrianus C. M.; Mitreva, Makedonka (Frontiers in Immunology, 2025)
BackgroundHelminth infections are widespread in resource-limited settings, and modulate host immune responses, with potential implications for viral coinfections. Intestinal helminths can alter susceptibility to respiratory viruses, but the mechanisms influencing SARS-CoV-2 infection outcomes remain poorly understood.MethodsUsing the Syrian hamster model, we investigated the impact of prior infection with the human hookworm Ancylostoma ceylanicum on host responses to SARS-CoV-2. Tissue-specific transcriptional responses were compared among four groups: naive, hookworm-only, SARS-CoV-2-only, and coinfected with both pathogens, 3 and 6 days post-viral infection. Viral titers and weight loss were assessed, and RNA-seq transcriptome profiles from lung and intestinal tissues were interrogated to identify differentially expressed genes and cellular pathways.ResultsPrior hookworm infection did not significantly alter viral titers or weight loss compared to SARS-CoV-2 infection alone, but distinct transcriptional signatures compared were identified compared to either single infection. Coinfection uniquely differentially regulated hematopoiesis and B cell-associated genes (e.g., ATF5, IGHM, JCHAIN) in the lungs, and immune and stress response pathways and inflammation-associated genes (e.g. FOLR2, PLA2GF, FABP3) in the intestine. Genes and pathways differentially regulated by SARS-CoV-2 alone, but with attenuated transcriptional responses in the lungs of coinfected hamsters were observed, including the loss of upregulation of toll-like receptor signaling and previously proposed host biomarkers for COVID-19 severity (CHI3L1, HMOX1), Long COVID (FCG4/FCGR3A and FST) and mortality (FST). In the intestine, hookworm-associated suppression of type I interferon-related genes (TAP1, IRF7) was reversed with SARS-CoV-2 coinfection, highlighting pathogen-specific modulation of innate antiviral signaling. Genes and pathways consistently differentially regulated by with SARS-CoV-2 were consistent with expectations, and many hemoglobin pathways were differentially regulated with hookworm in the intestine. CIBERSORT analysis was estimated relative leukocyte abundances in each sample cohort.ConclusionOur findings demonstrate that A. ceylanicum infection reshapes host transcriptional responses to SARS-CoV-2 in a tissue-specific manner, enhancing B cell immunity in the lung while driving intestinal inflammation. Hookworm-induced immune modulation attenuated key SARS-CoV-2-responsive genes and pathways, suggesting potential mechanisms for reduced disease severity observed in helminth-endemic regions. These findings establish a molecular framework to better understand helminth, SARS-CoV-2 and host immune interactions, with relevance for other respiratory viral infections.